On Foreignization’s Contribution to Spreading Chinese Language and Culture in Pearl S. Buck’s All Men Are Brothers - Wu, Shaoming (Pacific International Journal, 2023)
Nowadays, “Spreading China’s voice and telling Chinese stories” is a trend and the translation involving Chinese cultural publicity becomes a focus of domestic translation work. The use of foreignization strategy is conducive to the export of source language and culture. With the cultural turn of translation, especially in translation involving cultural factors, foreignization plays an increasingly important role in translation. As one of the four classics, Shui Hu Zhuan is publicly regarded as a masterpiece with great achievement both in the Chinese “good fellow” culture and typical Chinese language features. Amid translation versions of this book, Pearl S. Buck’s All Men Are Brothers is highly praised for spreading Chinese language and culture with foreignization strategy. Typical cases are chosen from Shui Hu Zhuan and its translation All Men Are Brothers to research foreignization strategy’s contribution to spreading Chinese language and culture abroad.